Answer:
We obtained the two exponential functions:
Explanation:
As we know that the exponential function is of the form
f(x) = abˣ
Given the points
We know these points belong to the exponential function.
so substituting the values (3, 7) and (5, 63) in the function
putting (3, 7)
y = abˣ
7 = ab³
also putting (5, 63)
y = abˣ
63 = ab⁵
Considering the 2nd equation
63 = ab⁵
as
![a^b* \:a^c=a^(b+c)](https://img.qammunity.org/2021/formulas/mathematics/college/otg0x2rencteitj0jzayw9ofa3hq79xa9r.png)
so
63 = ab³×b²
substituting 7 = ab³ in 63 = ab³×b²
63 = 7 × b²
b² = 63/7
b² = 9
b = ± 3
If b = 3
plug in b = 3 in the equation 7 = ab³ to find the value 'a'
7 = ab³
7 = a(3)³
7 = a × 27
a = 7/27
so, a = 7/27 and b = 3 would give us the function
y = abˣ
![y\:=\:(7)/(27)\left(3\right)^x](https://img.qammunity.org/2021/formulas/mathematics/college/yzsfftg7nruyoivcpota9qpg2pivubmnjj.png)
if b = -3
plug in b = -3 in the equation 7 = ab³ to find the value 'a'
![\:7\:=\:a\left(-3\right)^3](https://img.qammunity.org/2021/formulas/mathematics/college/56wejgxvlsgykx1vxcsqh5c2sxusr0sc1v.png)
![a\left(-27\right)=7](https://img.qammunity.org/2021/formulas/mathematics/college/n88yy28b572zat6nrwx3hpt07yt12jdaj4.png)
![a=-(7)/(27)](https://img.qammunity.org/2021/formulas/mathematics/college/gieqwcivt07xzcekd8p36fsv3h5xwza38x.png)
so, a = -7/27 and b = -3 would give us the function
y = abˣ
![y\:=-\:(7)/(27)\left(-3\right)^x](https://img.qammunity.org/2021/formulas/mathematics/college/s0694ss5spwbxck7ied6jk5uwd3s59e72n.png)
Thus, we obtained the two exponential functions: